Prospects for food demand and supply in Central Asia - Pandya-Lorch, Rajul; Rosegrant, Mark W. (Elsevier, 2000)
Central Asia has experienced massive economic and social shocks during the past decade following the dissolution of the former Soviet Union. Demand for cereals, particularly for staple cereals and meats, has fallen significantly even as production and productivity have plummeted. Although agricultural reforms were launched in 1991, the performance of the agricultural sector has been weak across the region. Prospects for food security in Central Asia appear mixed. Projections indicate that a growing and urbanizing population in Central Asia with rising incomes will increase demand for cereals by 32% between 1995 and 2020 to reach 24 million tons, and for meat by 47% to reach 2.9 million tons. Improvements in crop productivity will be essential to meet the increases in demand projected for the region. Cereal production is forecast to keep pace with demand such that Central Asia will be virtually self-sufficient in cereals. However, national food self-sufficiency or food security does not necessarily translate into household or individual food security. Moreover, self-sufficiency comes with a high price-tag of opportunities foregone and inappropriate use made of resources. Given the growing enthusiasm for food self-sufficiency in Central Asia, it is imperative that research be undertaken to assess the full costs and benefits of such a policy.